2020
DOI: 10.1073/pnas.2012347117
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically superior matrices promote osteointegration and regeneration of anterior cruciate ligament tissue in rabbits

Abstract: The gold standard treatment for anterior cruciate ligament (ACL) reconstruction is the use of tendon autografts and allografts. Limiting factors for this treatment include donor site morbidity, potential disease transmission, and variable graft quality. To address these limitations, we previously developed an off-the-shelf alternative, a poly(l-lactic) acid (PLLA) bioengineered ACL matrix, and demonstrated its feasibility to regenerate ACL tissue. This study aims to 1) accelerate the rate of regeneration using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…However, increasing evidence is mounting that changes in biomechanical loading due to increased body mass do not account for the severity of obesity-induced knee OA (1)(2)(3)(4)(5)(6)(7)(8)(9). These observations suggest that other factors related to the presence of adipose tissue and adipose tissue-derived cytokines-termed adipokines-play critical roles in this process and other musculoskeletal conditions (1,2,6,7,10). As there are presently no disease-modifying OA drugs available, direct evidence linking adipose tissue and cartilage health could provide important mechanistic insight into the natural history of OA and obesity and therefore guide the development and translation of novel OA therapeutic strategies designed to preserve joint health.…”
mentioning
confidence: 99%
“…However, increasing evidence is mounting that changes in biomechanical loading due to increased body mass do not account for the severity of obesity-induced knee OA (1)(2)(3)(4)(5)(6)(7)(8)(9). These observations suggest that other factors related to the presence of adipose tissue and adipose tissue-derived cytokines-termed adipokines-play critical roles in this process and other musculoskeletal conditions (1,2,6,7,10). As there are presently no disease-modifying OA drugs available, direct evidence linking adipose tissue and cartilage health could provide important mechanistic insight into the natural history of OA and obesity and therefore guide the development and translation of novel OA therapeutic strategies designed to preserve joint health.…”
mentioning
confidence: 99%
“…The critical pH for the dental hard tissues is believed to be at 5.5, below which the organic matrix begins to break and initiate demineralization. Similarly, for the deeper tissues at the periosteal level, slight pH changes can affect the healing and mineralization by affecting the cell activity [ 39 ]. We tested the buffering capacity (in lactic acid: pH = 4.0) of the Control against the zPACs in triplicate and observed that zPAC had a more steady change in pH.…”
Section: Resultsmentioning
confidence: 99%
“…The main actor in the progression of osteoarthritis is controversial, however a greater appreciation of the role adipose tissue (infrapatellar fat pad) plays in promoting osteoarthritis has recently garnered more interest ( Collins et al, 2021 ; Greif et al, 2020 ). Moreover, the combinatorial application of FGF-2 and FGF-8 in the knee joint was recently found to suppress adipokine secretion and demonstrated a decreased inflammatory profile ( Mengsteab et al, 2020 ). Evidence has begun to reveal that adipose tissue promotes inflammation within the knee, which leads to cartilage degeneration.…”
Section: Discussionmentioning
confidence: 99%